Evaluation of KCl-EDTA-, CaCl2- DTPA-, CaCl2-DTPA-TEA extractants for estimating available Cu in soils - Balláné Kovács, Andrea; Kincses, Sándorné; Nagy, Péter Tamás (Acta Agraria Debreceniensis, 2007)
KCl-EDTA-, CaCl2-DTPA-, CaCl2-DTPA-TEA extractionmethods were compared to determine the plant available Cuamounts in the soil samples. In the soil extracts, the amounts ofcopper were measurable. In the buffered CaCl2-DTPA-TEAextracts, data showed the lowest values.On the applied soils, a correlation was observed betweenplant removal and soil Cu using extractants mentioned above. Theclosest correlation appeared in the case of sandy soils.From the results of statistical analysis, it appears that soilproperties may play role in the efficiency of the extraction usingeither CaCl2-DTPA or KCl-EDTA solutions.To establish more reliable relations, further studies withdifferent types of soils are needed.